2021
DOI: 10.1155/2021/6684839
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia and Undernutrition of Adolescent Females in Selected Schools in Ghana

Abstract: Anemia among adolescent females is a major worldwide public health problem which should be given appropriate attention. Half of all anemic cases are caused by iron deficiency. In addition to anemia, poor nutrition is also a challenge in sub-Saharan Africa. This study determined the prevalence of anemia and undernutrition among adolescent females in school. A cross-sectional study was conducted among 151 adolescent females in four basic schools in the Ahafo region of Ghana. The hemoglobin level and anthropometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
3
7
0
2
Order By: Relevance
“…The prevalence of anaemia was determined by using a portable haemoglobin meter URIT 12 similar to a study conducted by Tandoh et al [22]. The prevalence of anaemia in this study was found to be 67.5% among women of reproductive age between the ages of 15-49.…”
Section: Discussionsupporting
confidence: 75%
“…The prevalence of anaemia was determined by using a portable haemoglobin meter URIT 12 similar to a study conducted by Tandoh et al [22]. The prevalence of anaemia in this study was found to be 67.5% among women of reproductive age between the ages of 15-49.…”
Section: Discussionsupporting
confidence: 75%
“…The development of ABE‐liposomes was conceived as a potential strategy for supplementation or fortification with highly bioavailable iron to prevent or treat iron deficiency anemia and/or its previous stages as deficiency. Thus, the present study could contribute to the fulfillment of two of the 17 Sustainable Development Goals of the United Nations, such as “zero hunger” by improving people's iron nutrition and “good health and well‐being”, since anemia affects 40% of the world's population, and has a negative effect on growth, cognitive development and academic performance, causes fatigue and low productivity, affecting the health and well‐being of the population (Tandoh et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, effective measures must be taken to eradicate this nutritional problem especially for increasing the quality of life. 7,15,35,36 Although the program administering iron supplements has been in place for a long time in Indonesia, the prevalence of iron deficiency anemia is still high, especially in rural areas. Nonetheless, there have been limited anemia studies specifically focused on the prevalence and causes of anemia among women and adolescent girls in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, effective measures must be taken to eradicate this nutritional problem especially for increasing the quality of life. 7 , 15 , 35 , 36 …”
Section: Introductionmentioning
confidence: 99%